(untitled) (2013)
The structural behavior of concrete masonry is strongly influenced by the mechanical properties of the constituent materials. The compressive strength of masonry is probably the most important parameter in the design of masonry structures, and it depends mainly on the strength of the individual blocks. However, the design code for masonry structures assumes linear-elastic behavior for the numerical models, which cannot provide an accurate prediction of the real structural behavior, thereby producing high uncertainty on the displacements. Currently, displacement based design approaches have been developed considering the stress-strain relationship as one of the most important parameter in order to control the structural response. In this work, a constitutive model has been developed in order to estimate the behavior of concrete blocks under uniaxial compression stress by means of the correlation between constitutive models and the experimental results corresponding to 90 samples of hollow concrete blocks. The results show that the strength of the blocks should be involved in the analytical model in order to obtain a good match with the experimental results.